2016
DOI: 10.1155/2016/8079372
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Long Noncoding RNA UCA1 as a Novel Biomarker of Acute Myocardial Infarction

Abstract: Acute myocardial infarction (AMI) is the most serious cardiovascular disease with high morbidity and mortality. Recent studies have showed that long noncoding RNAs (lnc RNA) play important roles in pathophysiology of cardiovascular diseases, but the investigations are still in their infancy. An lnc RNA named urothelial carcinoma-associated 1 (UCA1) is found in tumors such as bladder cancers and lung cancer. And the UCA1 could be as a predictive biomarker for bladder cancer in urine samples or lung cancer in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 26 publications
0
97
1
Order By: Relevance
“…LncRNA discrimination antagonising non-protein coding RNA (DANCR) encodes human chromosome 4q12 and it was firstly identified as epidermal cell differentiation suppressor [12], but further study revealed that it acted as an oncogene in various kinds of cancers, such as colon cancer [13], prostate cancer [14] and hepatocellular carcinoma [15]. However, the effect of DANCR in cardiovascular diseases has never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA discrimination antagonising non-protein coding RNA (DANCR) encodes human chromosome 4q12 and it was firstly identified as epidermal cell differentiation suppressor [12], but further study revealed that it acted as an oncogene in various kinds of cancers, such as colon cancer [13], prostate cancer [14] and hepatocellular carcinoma [15]. However, the effect of DANCR in cardiovascular diseases has never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, lncRNAs have been previously investigated for their potential role as cancer biomarkers in body fluids (either in plasma, serum or urine) [13][14][15][16][17][18]. For example, the lnc-RNA UCA1 (urothelial carcinoma associated 1) is a lncRNA revealed as a potential biomarker for bladder cancer [19], Also in prostate cancer patients, fragments from different regions of MALAT1 transcript were detected in plasma at higher copy number than in non-prostate cancer patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…The plasma concentration of the lncRNA CoroMarker was recently recognized as a novel biomarker for the diagnosis of coronary artery disease due to the stability, sensitivity and specific properties of CoroMarker in these patients [30]. The circulating concentration of the lncRNA UCA1 has also been identified as a potential novel biomarker for the prognosis of AMI [31]. These observations support the potential for lncRNAs to be used as biomarkers and therapeutics in ischaemic heart injury, especially AMI.…”
Section: Discussionmentioning
confidence: 83%